THE CONCEPTS OF SYNONYMY, INSYNONYMY AND ASYNONYMITY IN THE QUR'AN - HAMZANI, YUSRI (el-Umdah, 2024)
This article diverges from scholarly concerns over synonymity in the Qur'an. Frequently, the analysis of the word used in Al-Qur'an is commonly juxtaposed with its corresponding significance. The interpretation of the terminology in the Qur'an is frequently greatly influenced by the context and circumstances in which the verses are found. In order to address this academic worry, the author employs literature research approaches to conduct a comprehensive search for primary and secondary material. Upon completing many academic procedures, the author discovered a type of synonymy where two words possess identical meanings but differ in their pronunciations, such as the phrases ma?al and mi?l. The term's semantic connotation aligns with the phonetic analysis under consideration, and in actuality, the word is frequently regarded identically, regardless of its etymological source. Both names, n?r and ?iy?', have similar connotations of light, yet they differ in their meanings and origins. The term 'Adam al-tar?duf' is commonly employed by Qur'an scholars to denote this notion. Each word in the Quran has a unique and specific significance. When the individual components of a word are changed, even if they are very little, the meaning of the term is also changed. The misinterpretation of some sections in the Al-Qur'an by some readers can be attributed to their inability to comprehend its meaning.